2018
DOI: 10.5946/ce.2018.104
|View full text |Cite
|
Sign up to set email alerts
|

Magnified Endoscopic Findings of Multiple White Flat Lesions: A New Subtype of Gastric Hyperplastic Polyps in the Stomach

Abstract: Background/Aims:While the occurrence of multiple whitish flat elevated lesions (MWFL) was first reported in 2007, no studies on MWFL have been published to date. The present retrospective observational study aimed to clarify the endoscopic findings and clinicopathological features of MWFL. Methods:Subjects were consecutive patients who underwent upper gastrointestinal endoscopy as part of routine screening between April 2014 and March 2015. The conventional white-light, non-magnifying and magnifying narrow-ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Histologically, the biopsy specimens from the MWFLs included fundic gland parietal cell protrusions and oxyntic gland dilatations. There was no evidence of intestinal metaplasia 279…”
Section: Surveillancementioning
confidence: 95%
“…Histologically, the biopsy specimens from the MWFLs included fundic gland parietal cell protrusions and oxyntic gland dilatations. There was no evidence of intestinal metaplasia 279…”
Section: Surveillancementioning
confidence: 95%
“…Previous studies have shown that MUC5AC, which is specific for foveolar epithelium, was decreased by HP infection and increased by HP eradication [ 16 – 18 ]. Hyperplastic changes in the foveolar epithelium, such as multiple whitish flat elevated lesions (MWFL) [ 19 ], are frequently observed after HP-eradication [ 11 ]. In the present study, the frequency of WNM related to foveolar hyperplasia was significantly higher in HP-eradicated GCs than in HP-infected GCs.…”
Section: Discussionmentioning
confidence: 99%
“…In a current issue of Clinical Endoscopy , Hasegawa et al reported the ME-NBI and clinicopathologic findings of multiple whitish flat elevated lesions (MWFLs) extending from the gastric body to the fundus [7]. A previous study evaluating the endoscopic classification, using ME-NBI, of gastric precancerous and cancerous lesions proposed that lesions with tubular-villous mucosal and regular vascular patterns can be classified as IM [8,9].…”
mentioning
confidence: 99%
“…The common histologic findings of these lesions included straight enlarged foveolar epithelium with atrophy of the fundic gland without cystic dilatation. Hasegawa et al also reported observing foveolar hyperplasia in 100% of 4 patients, and parietal cell protrusion and oxyntic gland dilatation in 75% of the patients [7]. Fundic gland and hyperplastic polyps induced by proton pump inhibitor use have different histologic features from those of MWFLs.…”
mentioning
confidence: 99%
See 1 more Smart Citation